GE_GERICHTE P/13191/2017 vom 2. Oktober 2018 - GE Cour de justice (2018)
CONTRAVENTION ; PREUVE ; LOI FÉDÉRALE SUR LA PROTECTION DES ANIMAUX ; LÉSION CAUSÉE PAR LA CHALEUR ; AUTOMOBILE ; NÉGLIGENCE ; AMENDE | LPA.28.al2; CPP.398.al4; CPP.139.al2; LPA.4.al2; LPA.6.al1; CP.106